School-Based Management Innovation in Palangka Raya’s Islamic Elementary Schools - Syahmidi Syahmidi; Muhammad Redha Anshari; Mohammad Afifi; Saiful Lutfi (Jurnal Studi Guru dan Pembelajaran, 2025)
The development of information technology has accelerated digital transformation in education management, aiming to enhance efficiency, transparency, and stakeholder engagement. This study evaluates the implementation of a parent portal application in Islamic elementary schools in Palangka Raya City, focusing on its impact on school–parent communication, stakeholder participation, and School-Based Management (SBM). A mixed-methods approach was employed, involving quantitative surveys from 200 students and 50 teachers, and qualitative interviews with selected teachers, parents, and school administrators. The findings show that 85% of respondents agreed that the application improved communication, with a mean ease-of-access score of 4.3 (SD = 0.6). Teachers reported a 78% increase in parent participation, and there was a significant positive correlation between application usage and communication satisfaction (r = 0.65, p < 0.01). Factors supporting successful implementation included proactive leadership and ongoing digital training, while obstacles included infrastructure limitations, digital literacy gaps, and incomplete SOPs. The study concludes that digital transformation in SBM must be approached holistically, integrating technical, social, and managerial dimensions to ensure sustainability and improved education quality.